Inhibin B as a screening tool for early detection and treatment monitoring of central precocious puberty. (1st September 2020) - Jeong, Hwal Rim; Lee, Hye Jin; Shim, Yeong Suk; Kang, Min Jae; Yang, Seung; Hwang, Il Tae
Abstract: Anti-Müllerian hormone (AMH) and inhibin B are considered possible biomarkers of central precocious puberty (CPP). The aim of this study was to evaluate serum levels of AMH and inhibin B, to investigate their regulatory patterns, and to study their clinical significance in girls with CPP. In total, 48 girls with CPP and 35 age-matched prepubertal control girls were enrolled in the study. AMH and inhibin B levels were determined in the CPP and control groups. In the patient group, AMH and inhibin B levels were evaluated during 1 year of gonadotropin releasing hormone analog (GnRHa) treatment. The mean inhibin B level in the CPP group was significantly higher than that in the control. AMH levels were not different between the two groups. After GnRHa treatment. AMH and inhibin B levels decreased significantly. Based on the ROC analysis, the cutoff value for inhibin B to determine CPP was 19.59 pg/mL, with 83.3% sensitivity and 82.9% specificity, and the area under the curve was 0. 852. Inhibin B was useful for determining CPP and the therapeutic effects of GnRHa treatment in girls with CPP. AMH interacted, in part, with the hypothalamo-pituitary gonadal axis, but its clinical implications in CPP should be further investigated.